Pengaruh Pengelolaan Lingkungan dan Kenyamanan terhadap Kepuasan Wisatawan di Kampung Wisata Sawah - Deli Kristina Sidabutar; Rahmat Hidayat (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
In environmental cleanliness, there are many tourist attractions that do not maintain the cleanliness of the environment both from tourists and managers themselves. So that there needs to be awareness to maintain the environment around tourist destinations. This study aims to determine the effect of environmental management and comfort on tourist satisfaction. The sample of this study were 66 tourists of Kampung Wisata Sawah Pematang Johar, Kecamatan Labuhan Deli Kabupaten Deli Serdang Provinsi Sumatera Utara. The data analysis method used in this research is descriptive quantitative, while the data analysis model used in this research is multiple linear regression analysis. This hypothesis testing uses the coefficient of determination test, partial test and simultaneous test. The results of this study indicate that partially and simultaneously environmental management and comfort have no effect on tourist satisfaction in Kampung Wisata Sawah Pematang Johar. This study recommends that tourist attraction managers must maintain tourist satisfaction, especially in terms of managing the environment and comfort, so that this will increase the number of visits. Object managers must be able to manage Kampung Wisata Sawah Pematang Johar better so that the needs of tourists are met, and tourists can come back and even invite other tourists to come visit.